The sacrifice / 4 - Higson, Charles, 1958- (Higson, Charles, 1958- Enemy series, 2013)
"Follows the dual storylines of Small Sam on his search for Ella and of Shadowman's discoveries about Saint George and the Disease itself"--Provided by publisher.